Prevalence of Ehrlichia canis (Rickettsiales: Ehrlichieae) DNA in Tissues from Rhipicephalus sanguineus (Acari: Ixodidae) ticks in areas endemic for canine monocytic ehrlichiosis in Brazil - Oliveira, Bruno César Miranda [UNESP]; Ferrari, Elis Domingos [UNESP]; Viol, Milena Araúz [UNESP]; André, Marcos Rogério [UNESP]; Machado, Rosangela Zacarias [UNESP]; De Aquino, Monally Conceição Costa [UNESP]; Inácio, Sandra Valéria [UNESP]; Gomes, Jancarlo Ferreira; Guerrero, Felix D.; Bresciani, Katia Denise Saraiva [UNESP] (Oxford University Press (OUP), 2019)
Canine monocytic ehrlichiosis (CME) is a disease caused by the obligate intracellular bacterium Ehrlichia canis. Tropical lineages of Rhipicephalus sanguineus ticks play an essential role in the transmission of this pathogen. The aim of the present study was to evaluate the prevalence of E. canis DNA in tissue from R. sanguineus ticks in areas endemic for CME in Brazil and quantify levels of E. canis DNA in dissected tissues from these samples. A total of 720 ticks were collected from 72 dogs (36 dogs from the city Araçatuba in São Paulo state and 36 from Campo Grande in the state of Mato Grosso do Sul). Ticks were dissected to collect the guts, ovaries and salivary gland. A quantitative polymerase chain reaction (qPCR) targeting the disulphide bond formation (dsb) protein gene was performed to quantify the level of E. canis infection. The E. canis dsb-qPCR assay was positive for 31.9, 10, and 15.2% of the gut, ovary, and salivary glands, respectively. The average gut, ovary, and salivary gland bacterial load estimated by qPCR was 1.21 × 103, 2.60 × 103, and 4.92 × 103 gene copies/µl, respectively. This is the first report of E. canis DNA in ovaries of R. sanguineus ticks parasitizing dogs in these CME-endemic areas. These observations raise the possibility of E. canis trans-ovarial transmission.
Keywords: Ehrlichiosis; Tick; Tissue